1, 4‐Dihydropyridinebutyrolactone‐derived ring‐opened ester and amide analogs targeting BET bromodomains. Issue 11 (8th August 2022) - Jiang, Jiewei; Zhao, Pei‐Liang; Sigua, Logan H.; Chan, Alice; Schönbrunn, Ernst; Qi, Jun; Georg, Gunda I.
Abstract: Based on a previously reported 1, 4‐dihydropyridinebutyrolactone virtual screening hit, nine lactone ring‐opened ester and seven amide analogs were prepared. The analogs were designed to provide interactions with residues at the entrance of the ZA loop of the testis‐specific bromodomain (ZA) channel to enhance the affinity and selectivity for the bromodomain and extra‐terminal (BET) subfamily of bromodomains. Compound testing by AlphaScreen showed that neither the affinity nor the selectivity of the ester and lactam analogs was improved for BRD4‐1 and the first bromodomain of the testis‐specific bromodomain (BRDT‐1). The esters retained affinity comparable to the parent compound, whereas the affinity for the amide analogs was reduced 10‐fold. A representative benzyl ester analog was found to retain high selectivity for BET bromodomains as shown by a BROMOscan. X‐ray analysis of the allyl ester analog in complex with BRD4‐1 and BRDT‐1 revealed that the ester side chain is located next to the ZA loop and solvent exposed. Abstract : Ring‐opened ester and amide analogs of a 1, 4‐dihydropyridinebutyrolactone screening hit showed that esters retained affinity comparable to the parent compound, whereas the affinity for the amide analogs was reduced 10‐fold. A BROMOscan of benzyl ester 2e showed selectivity for the BET bromodomain family but no intra‐BET selectivity. In complex with BRD4‐1 and the first bromodomain of the testis‐specific bromodomain, the ester side chain of the allyl ester analog is located next to the ZA loop of the testis‐specific bromodomain loop and is solvent exposed.